Peran Masyarakat Sipil dalam Pemberantasan Korupsi : Pembelajaran dari Gerakan Nasional Penyelamatan Sumber Daya Alam (GNPSDA) - Epakartika, Epakartika; Murnawan, Rizky Nugraha; Budiono, Agung (Integritas : Jurnal Antikorupsi, 2019)
Civil society has an important role in fighting corruption agenda. This paper wants to describe and analyze how the role of civil society in to support The National Movement to Save Natural Resources activities were initiated by the Corruption Eradecation Commision (CEC) involving several other parties such as the Regional Government, Ministries/Institutions. This paper examines how involving the civil societies groups in efforts to improve the management of natural resources could have a positive impact not only in supporting corruption prevention and eradication work, but also encourages the evolution of the role of civil society from information providers to implementers in GNP SDA activities.